Mental health problems in pregnant and postpartum women living with HIV in sub-Saharan Africa: Systematic review and meta-analysis protocol. - Anthony Danso-Appiah; Kwadwo Owusu Akuffo; David Owiredu (PLoS ONE)
Background Existing evidence on the burden of mental health problems among pregnant and postpartum women living with HIV, a vulnerable population in sub-Saharan Africa (SSA), is limited and fragmented, affecting the development of context-sensitive and integrated interventions. This systematic review aims to provide an up-to-date and comprehensive synthesis of available evidence to estimate the burden and identify the determinants of mental health problems among pregnant and postpartum women living with HIV across countries in sub-Saharan Africa. Methods We will retrieve all relevant studies (published and unpublished) through searches in PubMed, Embase, PsycINFO, CINAHL, LILACS, Google Scholar, Scopus and Web of Science from inception to 30th June 2024, without language restriction. We will use the following search terms 'mental health disorder', 'mental health problem', 'pregnant women', 'postpartum women' and 'HIV' nested with all applicable alternate terms and the names of countries in SSA for running the searches. We will also search HINARI, African Index Medicus, African Journals Online, Academic Search Premier, medRxiv, ProQuest, EBSCO Open Dissertations, and reference lists of relevant studies. We will contact experts in the field for potentially relevant unpublished studies. All retrieved articles from the electronic databases and grey literature will be collated and deduplicated using Endnote and exported to Rayyan QCRI. Two reviewers will independently select studies using a pretested study selection flow chart developed from the pre-specified eligibility criteria. Two reviewers will extract data using a pretested data extraction form and assess the risk of bias in the included studies using the risk of bias tool for prevalence studies by Hoy et al. (2012). Any disagreements will be resolved through discussion between the reviewers. Binary outcomes (prevalence and incidence of mental health problems among pregnant and postpartum women living with HIV) will be evaluated using pooled proportions (for non-comparative studies) and odds ratio (OR) or risk ratio (RR) (for comparative studies), and mean difference for continuous outcomes, all will be reported with their 95% confidence intervals (CIs). Heterogeneity will be assessed graphically for overlapping CIs and statistically using the I2 statistic. If substantial heterogeneity is found, random-effects model meta-analysis will be performed; otherwise, fixed-effect meta-analysis will be employed. We will conduct subgroup analysis (to assess the impact of heterogeneity) and sensitivity analyses to test the robustness of the generated effect estimates to the quality domains. The overall level of evidence will be assessed using GRADE (Grading of Recommendations, Assessment, Development, and Evaluations). Expected outcomes The review is expected to produce an up-to-date and comprehensive synthesis of the available evidence, allowing for the generation of country-specific estimates of the burden of mental health problems among mothers living with HIV across SSA populations. Also, the review will attempt to identify the determinants of mental health problems among pregnant and postpartum women living with HIV, to shed light on the factors that contribute to the occurrence of mental health problems in this vulnerable population. Systematic review registration The systematic review protocol has been registered in the International Prospective Register for Systematic Reviews (PROSPERO), with registration ID CRD42023468537.